1986
DOI: 10.1530/acta.0.1110264
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sleep stages and plasma cortisol: a single case study

Abstract: The relationship between the plasma cortisol level and sleep stages was investigated in a single male subject across 17 nights. Blood samples were taken every 30 min from 11.00 p.m. until 02.30 a.m. and every 15 min during the rest of the night. Data analyses performed for the whole nights did not give evidence for strong relations between plasma cortisol and sleep stages. Analyses on data of the second part of the night, beginning with the onset of the first cortisol peak, revealed that plasma cortisol was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
8
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
5
8
0
Order By: Relevance
“…As dexamethasone, it tended to increase the time awake and the move ment time. These findings are in line with previous reports of a wakening effect of the endogenous cortisol [Alford et al, 1973;Born et al, 1986;Fehm et al, 1986;Follenius et al, 1985]. The infusion of hydrocortisone also reduced REM sleep.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As dexamethasone, it tended to increase the time awake and the move ment time. These findings are in line with previous reports of a wakening effect of the endogenous cortisol [Alford et al, 1973;Born et al, 1986;Fehm et al, 1986;Follenius et al, 1985]. The infusion of hydrocortisone also reduced REM sleep.…”
Section: Discussionsupporting
confidence: 93%
“…Results from experiments in animals and humans give some support that influences of glucocorticoids on the central nervous activity are not limited to negative feed-back regulation of the pituitary-adrenal axis, but pertain to major psychophysiological functions of the brain, as perception and sleep [Henkin, 1975;Beckwith et al, 1983;Weitzman et al, 1983;Fehm et al, 1984;Rees and Gray, 1984], In earlier studies Bom et al, 1986], we have demonstrated that the early morning rise in plasma cortisol is associated with a period of more shallow sleep, which was also in line with findings by Alford etal. [1973], Elevated nocturnal levels of adrenal cortical steroids may be also responsible for sleep disturbances typically observed in patients with endogenous depression [Jarret et al, 1985;Sachar et al, 1970].…”
supporting
confidence: 90%
“…Both rhythms are apparently coupled as suggested by the significant association between decreasing cortisol levels and REM sleep occurrence. This temporal relationship between plasma cortisol concentrations and REM sleep occurrence has been repeatedly observed by us [12][13][14] and other investigators [16]. The more detailed analysis performed in this study revealed that the asso ciation between decreasing cortisol concentrations and REM sleep was not present unequivocally for the whole sleep episode but was restricted to the second and third sleep cycles.…”
Section: Discussionsupporting
confidence: 81%
“…In our studies, the episodes of cortisol secretion appeared to be synchronized to sleep cycles with significant correlations be- Received: February 22, 1990 Accepted after revision: August 6, 1990 tween the occurrence of REM sleep and decreasing cortisol concentrations [12][13][14], These conflicting conclusions led us to reinvestigate the temporal relationship between sleep processes and adrenocortical secretion. We attempted to determine the periodicity of plasma cortisol concentrations for a comparison with the NREM-REM periodicity, and to decide whether or not both rhythms are coupled.…”
mentioning
confidence: 88%
“…The afferent humoral system exerts significant effects on human brain activity. From previous experiments in animals and humans it can be concluded that endogenous glucocorticoid actions on the central nervous system are not limited to negative feed-back regulation within the hypothalamus-pituitary-adrenal system, but also con¬ cern major psychophysiological processes as per¬ ception and sleep (Henkin 1975;Beckwith et al 1983;Rees & Gray 1984;Fehm et al 1986). Thus, endocrine disorders characterized by disturbances of corticosteroid secretion are often associated with concurrent changes in the course of sleep (e.g.…”
mentioning
confidence: 99%